Non-Magnetic Assembly Technology and Mechanical Performance Analysis of Permanent Magnet Integrated Motor for Ball Mills - Jun Gao; Xueyan Han; Zhongliang An; Zhanyang Yu (Energies)
The permanent magnet integrated motor (PMIM) for ball mills has the problems of difficult assembly and poor air gap uniformity adjustment due to the magnetic pull force in the conventional magnetic assembly. In this study, a non-magnetic assembly technology based on the installation of a permanent magnet after assembly was first proposed, and the analytical models of conventional magnetic assembly and non-magnetic assembly were established. On this basis, combined with the finite element method, the mechanical performance difference between the two assembly methods in the assembly, lifting, and centering stages were compared and analyzed. In addition, a device for adjusting the air gap was designed for the non-magnetic assembly technology, and the stress and deformation of the structure of this device were analyzed. The results showed that the total assembly load by using the non-magnetic assembly technique was significantly reduced by 71.8%, the maximum stress in the assembly process was reduced by 66.3%, and the maximum deformation was reduced by 66.7%, which significantly reduced the difficulty of assembly. Finally, a 210 W permanent magnet integrated motor for ball mills was designed and successfully assembled, which proves the effectiveness of the assembly technology.